New Record of Marine Wood-Borer Species in Mangrove Forest of Nusa Lembongan, Bali, Indonesia - Ketut, Ginantra; Made Saka, Wijaya; Ida Ayu, Astarini; Khairul Adha, A. Rahim (The Journal of Hunan University Natural Sciences, 2022)
Research has been carried out on the presence of wood-borer species in the mangrove forest of Nusa Lembongan, in May-June 2022. The study was conducted at five representative sites of mangrove forests in Nusa Lembongan. The data collection of the mangrove wood-borer was carried out by purposive sampling, which directly searches for dead mangrove stems, twigs, or roots that were attacked by the marine wood-borer found at each site. A total of There were new record four species of mangrove wood-borer, namely, Phaenops sp. beetle group (Coleoptera) and Cenoloba sp. moth group (Lepidoptera), two species of Mollusks, namely, Bankia minima and Bactronophorus sp. were identified. The larval stages of Phaenops sp. were found within the dead mangrove stems of Rhizophora apiculata and Sonneratia alba. Cenoloba sp. which was found in the larvae phase, the host plant was the dead stems of the mangrove Sonneratia alba. Bankia minima, the host plants are dead stems of mangroves Sonneratia alba, Rhizophora apiculata, Rhizophora stylosa and Avicennia sp. Bactronophorus sp., the host plant is dead wood from the mangrove Sonneratia alba, Rhizophora apiculata. The most widely distributed wood-borer species in the mangroves of Nusa Lembongan is Bankia minima. The results showed that four species of marine wood-borer are new records in the mangrove forest of Nusa Lembongan.